Computer-based and online rehabilitation therapy for depression and anxiety management: A case study of Jordanian parents of children with special needs - Al-Takhayneh, Suhaib Khaled; AlTarawneh, Rodaina Khader; Al-Mahameed, Amjaad Salameh Ali; Al-Shawawreh, Shadi Y; Al-Garalleh, Abdulnaser (Nurture, 2023)
Purpose: The present study aims to investigate the effectiveness of computer-based and online rehabilitation therapy in managing depression and anxiety among Jordanian parents of children with special needs as well as explore the underlying psychodynamic mechanisms involved in the therapeutic process. Design/Methodology/Approach: The sample size consisted of 337 participants who were randomly assigned to either the experimental group (receiving computer-based and online rehabilitation therapy) or the control group (receiving traditional therapy). Data were collected through self-reported questionnaires assessing depression and anxiety levels as well as psychodynamic variables such as defense mechanisms and attachment styles. Findings: The relationship between the variables was examined by Partial least squares (PLS) analysis. Results indicated that computer-based and online rehabilitation therapy was effective in reducing levels of depression and anxiety among Jordanian parents of children with special needs to facilitate changes in defense mechanisms and attachment styles indicating the involvement of psychodynamic processes in the therapeutic process. Conclusion: The findings suggest that computer-based and online rehabilitation therapy may be a valuable resource for managing depression and anxiety in Jordanian parents of children with special needs and provide insight into the underlying mechanisms involved in psychodynamic therapy. Research Implications: The field of psychological counselling is being advanced by the current research which has several theoretical and practical implications. This study is significant because it provides key policy insights on how to enhance attractiveness. Research efforts when developing programs need to be in line with technical advancements.